2021
DOI: 10.1111/nph.17180
|View full text |Cite
|
Sign up to set email alerts
|

Root growth responses to mechanical impedance are regulated by a network of ROS, ethylene and auxin signalling in Arabidopsis

Abstract: The growth and development of root systems is influenced by mechanical properties of the substrate in which the plants grow. Mechanical impedance, such as by compacted soil, can reduce root elongation and limit crop productivity. To understand better the mechanisms involved in plant root responses to mechanical impedance stress, we investigated changes in the root transcriptome and hormone signalling responses of Arabidopsis to artificial root barrier systems in vitro. We demonstrate that upon encountering a b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 94 publications
2
17
0
Order By: Relevance
“…The typical responses of roots encountering an obstacle are a reduction of root growth and a resulting "step-like" growth pattern, with only the root tip remaining in contact with the barrier surface. By RNA-seq approaches performed on whole roots of Arabidopsis seedlings collected either 6 or 30 h after barrier contact, combined with reporter line and mutant studies, Jacobsen et al [130] showed significant changes in reactive oxygen species (ROS), ethylene and auxin signaling pathways, confirming several previous studies. In particular, they demonstrated that when ethylene signaling is perturbed in ethylene-insensitive mutants, the root growth is less inhibited than in WT after barrier contact.…”
Section: Mechanosensitive Channel Expression In the Root Tipsupporting
confidence: 73%
“…The typical responses of roots encountering an obstacle are a reduction of root growth and a resulting "step-like" growth pattern, with only the root tip remaining in contact with the barrier surface. By RNA-seq approaches performed on whole roots of Arabidopsis seedlings collected either 6 or 30 h after barrier contact, combined with reporter line and mutant studies, Jacobsen et al [130] showed significant changes in reactive oxygen species (ROS), ethylene and auxin signaling pathways, confirming several previous studies. In particular, they demonstrated that when ethylene signaling is perturbed in ethylene-insensitive mutants, the root growth is less inhibited than in WT after barrier contact.…”
Section: Mechanosensitive Channel Expression In the Root Tipsupporting
confidence: 73%
“…Thus, the roots need to continuously adjust their morphological structures to respond to ever-changing local soil environments. The physically impeded roots display diverse morphological alterations, such as inhibition of root elongation and increase of radial dimension, resembling the morphological changes observed when roots are grown in the presence of ethylene ( Jacobsen et al, 2021 ). Consistent with these observations, when ethylene biosynthesis or signaling is repressed, the degree of root response to mechanical impedance is significantly alleviated ( Santisree et al, 2011 ).…”
Section: Ethylene Signaling Is Required For Root Adaption To Soil Barriermentioning
confidence: 83%
“…Similarly, ethylene signaling and ethylene-triggered downstream auxin and ROS signaling act together in the inhibition of root hair growth caused by boron deficiency, as evidenced by genetic and chemical treatment analyses [ 156 , 157 ]. Moreover, auxin, ethylene, and ROS also cooperate in regulating root architecture in response to mechanical impedance stress [ 158 ].…”
Section: Ethylene and Auxinmentioning
confidence: 99%